Analisis Pengaruh Usia Remaja Terhadap Kejadian Kekurangan Enegi Kronik (KEK) Pada Ibu Hamil Di Posyandu Flamboyan - Afrianti Afrianti; Resi Galaupa (Jurnal Keperawatan Muhammadiyah, 2023)
Background: The most common is chronic energy deficiency (KEK). SEZ is characterized by an upper arm circumference (LILA) <23.5 cm or a body mass index <18.5 kg/m². KEK in preconception women can cause health problems. Research Objectives: This study aims to analyze the influence of adolescent age on the incidence of birth defects in pregnant women at the Flamboyan Health Center. Research Methods: This study uses a correlation descriptive survey research design with a cross sectional approach. This research will be carried out at Diposyandu Flamboyan with a total sample of 40 respondents who meet the criteria. The sampling technique in this study was purposive sampling. Research Results: There is a relationship between adolescent age and the incidence of CED in pregnant women at Posyandu Flamboyan in 2023 using the chi squart test to obtain a p value = 0.001, which means it is smaller than a = 0.05. Conclusion: There is an influence of teenage age on the incidence of CED in pregnant women at Posyandu Flamboyan in 2023 with a significance level of 0.002 which is less than (5%) and has a negative regression coefficient of -2.457.